KEPENTINGAN THE UNITED NATIONS FRAMEWORK CONVENTION ON CLIMATE CHANGE (UNFCCC) MEMILIH WORLD BANK SEBAGAI PEMEGANG DANA THE GREEN CLIMATE FUND - Pratiwi, Gizka Ayu; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a study of conflict of interest which discusses about the interest of The United Nations Framework Convention on Climate Change on chosing the World Bank as the shareholders of the Green Climate Fund. The climate change has been a crucial issue that should be solved wisely. Many efforts had been tried for solving this issue, until the countries agree for making an operating entity of the financial mechanism of the convention (The Green Climate Fund) through the Conference of Parties of UNFCCC.This funding mechanism requires all developed and developing country to take their part in making the success of it.In this research, the author uses the group behavior analysis level which focused on the role of international organization. This research uses the diplomacy theory by Woodrow Wilson and the decision making theory, which are explain how the procedure for the decision is choosen.In effort to succeed this new agenda of UNFCCC, some critical statement come because the fact that, there are many developed countries that still using the dirty energy, which is the high factor of carbon emissions producer. The record of World Bank career in funding the countries which support and produce the dirty energy, also being one of the critic and obstacle. And the using of dirty energy of them still had increased right after the program declaration.Keywords: The United Nations Framework Convention on Climate Change (UNFCCC), The Green Climate Fund (GCF), World Bank, Climate Change, Interest,